2003
DOI: 10.19182/remvt.9863
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation zootechnique des ovins de race Sardi au Maroc

Abstract: Un total de 811 performances de reproduction, 1 430 poids de toison, 1 024 performances de croissance et de viabilité, et 154 performances d’engraissement et d’abattage des ovins de race Sardi ont été analysées. Ces performances ont été collectées durant sept campagnes allant de 1993-1994 à 1999-2000 au domaine expérimental de Déroua à l’Institut national de la recherche agronomique. L’analyse des données a montré que les brebis avaient une durée de la gravidité de 151 jours, un taux de fertilité de 98 p. 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Body weight at puberty in Tazegzawt ram lambs (43.1±5.47 kg) appeared to be lower than those reported in Saidi ram lambs (50.3±3 kg [ 24 ]) but closer to those in Ouled Djellal ram lambs (40.4±1.2 kg [ 21 ]), Libyan fat-tailed ram lambs (39.9±9.3 kg [ 11 ]), and Suffolk sheep (36.8 kg; [ 20 ]). Lower body weights at puberty are also reported with 32.5 kg in Clun Forest sheep [ 7 ], 33.1 kg in Rahmani sheep [ 25 ], 24-29 kg in Merino sheep [ 9 ], and 23.7 ± 0.94 kg in Romanov sheep [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Body weight at puberty in Tazegzawt ram lambs (43.1±5.47 kg) appeared to be lower than those reported in Saidi ram lambs (50.3±3 kg [ 24 ]) but closer to those in Ouled Djellal ram lambs (40.4±1.2 kg [ 21 ]), Libyan fat-tailed ram lambs (39.9±9.3 kg [ 11 ]), and Suffolk sheep (36.8 kg; [ 20 ]). Lower body weights at puberty are also reported with 32.5 kg in Clun Forest sheep [ 7 ], 33.1 kg in Rahmani sheep [ 25 ], 24-29 kg in Merino sheep [ 9 ], and 23.7 ± 0.94 kg in Romanov sheep [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, body weight, thoracic and SCs, penile development stages, and seminal parameters were considered to investigate puberty onset. Tazegzawt ram lamb presented a significant growth potential, at birth, lambs weighed 5.2±0.7 kg, and values were lower than those reported in Redkaraman lambs (5.6±0.33 kg [ 1 ]) but higher than those of several breeds including Bharat Merino (3.2±0.03 kg [ 15 , 16 ]), Romanov (2.5±0.18 kg [ 18 ]), Sardi (4.1 kg, [ 18 ]), D’Man (2.8±0.65 kg [ 16 ]), and Ouled Djellal (4.5±0.7 kg [ 19 ]), an Algerian breed which showed at one year age an average daily gain of 104.2±23.1 g/day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of this study are well above the mean values reported by Kerfal et al(2005) in the D'man breed : 7.69 kg and 19.8 kg at 30 and 90 days, respectively, by Rekik et al (2008) in the same breed : 3.4 Kg, 5.9 Kg, 11.4 Kg, 13.1 Kg, at 10, 30, 70 and 90 days, respectively, with a ADGs of 100 g/d between the age of 10 and 30 days, by Chikhi and Boujenane (2003) in the Sardi breed, the most important Moroccan breed : 10.9 kg, 22.5 kg and 35.7 kg at 30, 90 and 180 days, respectively with a ADGs of 224 g/d between 0-30 days and 194 g/d between 30 and 90 days and by Boujenane and Kansari (2005) in the Timahditebreed : 9.56 kg and 17.9 kg at 30 days and 70 days respectively.…”
Section: Weight and Growth Ability Of Lambsmentioning
confidence: 88%
“…The results obtained are near to the rates calculated from the results of surveys by Hambli and Tazarat, (2003) in the Tazegzawt breed: 72% and 154%, for fertility and prolificacy, respectively. Under the same breeding conditions, the ewe's fertility recorded in this study is comparable to that of the standards of local sheep breeds : 89% for OuledDjellal (IANOR, 2007a), 90% for Rembi, (IANOR, 2013), 86% for the Hamra breed (IANOR, 2007b), of the Black Tunisian race of Thibar : 90.5% (Hammami et al, 2014), of the Boujaâd breed : 89%, (El Fadili, 2008) and of the BeniGuil breed : 91% (El Fadili, 2009).Nevertheless, the Tazegzawt ewe is less fertile than the Sardi breed : 98% (Chikhi and Boujenane, 2003), while the prolificacy is much higher compared to the OuledDjellal breed : 110% (IANOR, 2007a), Rembi: 115% (IANOR, 2013), Hamra : 115% (IANOR, 2007b), Sardi : 129% (Chikhi and Boujenane, 2003), Boujaâd : 109% (El Fadili, 2009), Black Tunisian Thibar: 120% (Hammami et al, 2014), the Merino breed of Rambouillet : 123% (Anonymous, 2010) and Timahdite: 105% (Boujenane and Kansari, 2005) but comparable to that of Lacaune : 175% (Babo, 2000).…”
Section: Reproductive Performancementioning
confidence: 99%